An Inquiry in the Information Needs of Iran’s South Khorasan Public Library Users by Means of Hill’s Model - Mohammad javad Hashemzadeh; Masoomeh faramarzi (تحقیقات اطلاع‌رسانی و کتابخانه‌های عمومی, 2016)
Purpose: This study aims to find information needs of users of the public libraries in Iran’s South Khorasan province based on Hill’s user study model. Methodology: survey method was used to perform the research. The population included all accredited members of the public libraries in Iran’s South Khorasan Province until the end of 2012 August 2 with an estimated number of 23594 members. Reliability of questionnaire was measured by Chronbach’s alpha and validity of it was approved by related faculty members of universities. The data were analyzed using independent two sample t-test and One-way ANOVA test. Findings: Most users of the public libraries in Iran’s South Khorasan Province had high school diploma, B.A. and BSC degrees and one third of the total sample population received their ICDL certifications. The users claimed that their information literacy skills are above the mean level. Their most important needs were supplementary reading materials for education, literature, and religion. Most important motivations for using libraries were doing homework, classroom projects, and increasing their public information level respectively. Outdated resources, scarcity of information materials and the lack of internet access were the most significant obstacles to meet users' information needs. The libraries sources and services moderately satisfied the users' needs. Users’ information needs significantly vary in Gender and education level factors.